The role of Tripterygium wilfordii extract in weight loss, energy expenditure, glucose and lipid metabolism - Mele, Mahdi Mousavi; Nachvak, Mostafa; Asghari-Jafarabadi, Mohammad; Alipour, Beitallah; Zohourtabar, Amin; Fasihi, Mehdi (Progress in Nutrition, 2018)
Introduction: Obesity is a chronic disease that characterized by the disturbance of the body composition, which is expressed as the relative or absolute increase in the amount of adipose tissue. Tripterygium wilfordii is an herbaceous plant of the Celastraceae family which is widely used in China. The roots of this plant have many therapeutic properties. Recently in animal studies, it has been shown that Celastrol in the root of Tripterygum wilfordii has been associated with weight loss, suppression of food intake, and increased leptin sensitivity. Triptolide is another effective ingredient in this plant, has significantly reduced TG, TC, LDL-C and weight loss in animal models. Also, Celastrol has an anti-obesity effect in ob/ob mice, which reduces the intake of food and the percentage of body fat. Materials and methods: Searching for articles based on Electronic databases including Google Scholar (scholar.google.com), Pub Med (www.ncbi.nlm.nih.gov/pubmed), (Science Direct (, and Springer (www.springer.com) until November 2017. Results: The use of celastrol significantly reduces dietary intake and body mass in mice. Celastrol increased the energy expenditure (EE) and reduced the amount of respiratory exchange ratio (RER) in the mice. celastrol caused a very marked decrease in plasma cholesterol, triglyceride and LDL levels, as well as a significant increase in plasma HDL levels. also, triptolide reduces serum cholesterol, TG and LDL. Discussion: It Can be considered, Tripterygium wilfordii roots may be consumed as a therapeutic compound that prevents obesity and complications associated with this disease.